The origin and evolution of emerged swine acute diarrhea syndrome coronavirus with zoonotic potential - Yu, De; Zhao, Zhuang‐Yan; Yang, Yong‐Le; Qin, Yu; Pan, Dan; Yuan, Li‐Xia; Huang, Yao‐Wei; Wang, Bin (Journal of medical virology, 2023)
Swine acute diarrhea syndrome coronavirus (SADS‐CoV) is a newly discovered alphacoronavirus with zoonotic potential that causes diarrhea and vomiting mainly in piglets. Having emerged suddenly in 2017, the prevailing opinion is that the virus originated from HKU2, an alphacoronavirus whose primary host is bats, and at some unknown point achieved interspecies transmission via some intermediate. Here, we further explore the evolutionary history and possible cross‐species transmission event for SADS‐CoV. Coevolutionary analysis demonstrated that HKU2 may have achieved host switch via SADS‐related (SADSr)‐CoV, which was isolated from the genus Rhinolophus in 2017. SADS‐CoV, HKU2, and SADSr‐CoV share similar codon usage patterns and showed a lower tendency to use CpG, which may reflect a method of immune escape. The analyses of virus‐host coevolution and recombination support SADSr‐CoV is the direct source of SADS‐CoV that may have undergone recombination events during its formation. Structure‐based spike glycoprotein variance analysis revealed a more nuanced evolutionary pathway to receptor recognition for host switch. We did not find a possible positive selection site, and the dN/dS of the S gene was only 0.29, which indicates that the current SADS‐CoV is slowly evolving. These results provide new insights that may help predict future cross‐species transmission, and possibly surveil future zoonotic outbreaks and associated public health emergencies.